Vladimir Vladimirovich Nabokov and Jason Epstein: A Study in Authorial Extravagance and Editorial Restraint - Tock, Emily (Journal of Scholarly Publishing, 2017)
Studying the relationship between author and editor provides valuable insight into the biography of the author and into the role that publishing plays in the creation of literary works; as such, delving into the publication history of Vladimir Nabokov's writing informs the continuing discussion of his work as an author and the publisher's role in the creation and dissemination of that work. This article discusses the relationship between Nabokov and his editor at Doubleday and Company, Jason Epstein, who worked extensively with Nabokov on several of his books.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDguNC4yNjg